Symptomatic Intracerebral Hemorrhage Complicating Intra-Arterial Mechanical Thrombectomy in Acute Ischemic Stroke - Amran, Muhammad Yunus; Bahar, Ashari (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Acute ischemic stroke (AIS) is the most common type of stroke. The endovascular treatment of AIS depends on stroke subtype, whether caused by large vessel occlusion (LVO) or not. We presented a case of AIS due to LVO that has complication in the form of symptomatic intracerebral hemorrhage (sICH) after an intra-arterial mechanical thrombectomy. CASE PRESENTATION: An 80-year-old woman was admitted to the emergency department with sudden onset left side weakness since <1 h before admission, when the patient had woke up in the morning. The patient had history of hypertension, diabetes mellitus, and dyslipidemia. She also had cardiac disorders in the form of non-valvular atrial fibrillation with 55% left ventricular ejection fraction (LVEF). Her blood pressure was 148/84 mmHg, heart rate was 65 beats/minute, respiratory rate was 17 times/min, and body temperature was 36.2°C. Glasgow coma scale (GCS) was E3V4M5; National Institutes of Health Stroke Scale (NIHSS) was 15. She had moderate aphasia. Head CT scan did not show any hyper- or hypodens areas and Alberta Stroke Program Early CT score was 10. RAPID automated CT perfusion using Quantitative Software showed that the mismatch volume was 192 ml and the mismatch ratio was 7.4. Endovascular therapy in the form of intra-arterial mechanical thrombectomy was performed, and blood flow in the right internal carotid artery (ICA) was restored with the score of Modified Thrombolysis in Cerebral Infarction (mTICI) was III. Follow-up non-contrast head CT scan was performed and revealed acute infarction with hemorrhagic transformation in the middle cerebral artery (MCA) territory. CONCLUSION: Early and accurate treatment of AIS is paramount. Endovascular treatment in the form of intra-arterial mechanical thrombectomy is the current treatment recommendation in LVO although there is a risk of symptomatic intracerebral hemorrhage, as in this case.